Imagery ability in Boccia: comparison among federate athletes from different medical sport groups - Amorim, André (2018)
Submitted by iria pinto (iria@ipcb.pt) on 2018-02-02T16:46:35Z No. of bitstreams: 1 11780-42490-1-PB.pdf: 488543 bytes, checksum: c71ea65d50f54ba886fcacfc51ca474e (MD5)